<u>Answer:
</u>
Required five terms of sequence are 19 , 12 , 5 , -2 and -9 .
<u>
Solution:
</u>
Need to find the five terms of the sequence.
Given recursive rule is f(x) = f(x-1) -7
Substituting x = 2 , f(2) = f(2-1)-7
= f(2) = f(1) – 7 ------(1)
Also given that f(2) = 12.
On substituting the given value of f(2) in eq (1) we get
12 = f(1) – 7
f(1) = 12 + 7 = 19
Using given recursive rule and given value of f(2) calculating f(3)
Substituting x = 3 ,
f(3) = f(3-1) – 7
= f(2) – 7
= 12 – 7
= 5
Using given recursive rule and calculated value of f(3) calculating f(4)
Substituting x = 4,
f(4) = f(4-1) – 7
= f(3) – 7
= 5– 7
= -2
Using given recursive rule and calculated value of f(4) calculating f(5)
Substituting x = 5,
f(5) = f(5-1) – 7
= f(4) – 7
= -2– 7
= -9
Hence required five terms of sequence are 19 , 12 , 5 , -2 and -9 .
We know that we are solving for y.
This is a step by step procedure to get the value of y.
First: Move all terms to the left side and set equal to
zero.
Second: Then set each factor equal to zero.
The application is:
Given: py+7=6y+q
-6y -7 -6y -7 = 0
(p-6)y = q-7
divide both sides by p-6
y=(q-7)/(p-6)
Answer is y = (q – 7) / (p – 6)
Answer:
x/520 = 5/13
Step-by-step explanation:
I took a test with this question on it.
Answer:
48y⁶w¹¹
Step-by-step explanation:
[-3y⁵][4y] → -12y⁶
×
[w³][-4w⁸] → -4w¹¹
______
48y⁶w¹¹
I am joyous to assist you anytime.